Digital media and its impact on bringing about value change among young people - Mehenni, Samy Ali; Messaoudene, Ahmed (Journal of Ecohumanism, 2025)
The world today is witnessing significant developments in information and communication technologies, one of whose manifestations is the emergence of a new type of media as an alternative to traditional media, namely digital media. The latter has become an essential part of young people’s lives, particularly with the increasing reliance of youth on it and their use of its various digital platforms. Due to its widespread diffusion among young people, transformations have begun to appear in their behaviors and values, as well as changes in the system of social, cultural, and religious values within this group, as a result of their engagement with and continuous exposure to digital media.